2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology 2011
DOI: 10.1109/wi-iat.2011.250
|View full text |Cite
|
Sign up to set email alerts
|

Improving Retrieval of Future-Related Information in Text Collections

Abstract: Abstract-People often want to know expected future events related to given real world entities. For supporting users in the process of future scenario analysis, we propose several methods that enable to retrieve and analyze future-related opinions from large text collections. In particular, we focus on time-unreferenced predictions, which do not contain any explicit future time reference and hence are more difficult to be retrieved. As a second contribution, we propose estimating the validity of predictions by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Therefore, a future topic/event is extracted only if it is mentioned together with some dates in the future. In fact, news articles also contain many references to future topics and events without mentioning when they are likely to happen [5]. The advantage of considering only time-referenced topics and events is that they allow us to estimate probability distributions over the timeline, and these references are more probable and credible as the time at which they will happen is more or less decided or agreed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a future topic/event is extracted only if it is mentioned together with some dates in the future. In fact, news articles also contain many references to future topics and events without mentioning when they are likely to happen [5]. The advantage of considering only time-referenced topics and events is that they allow us to estimate probability distributions over the timeline, and these references are more probable and credible as the time at which they will happen is more or less decided or agreed.…”
Section: Discussionmentioning
confidence: 99%
“…Time Explorer [8] is a search engine that lets users search in the future and analyze future evolution of topics. Kanazawa et al [5] describe methods for retrieval and validity analysis of future-related information which is not associated with explicit future dates. Our task is different from the above works as we focus on estimating the probability of events based on the aggregated evidence of future-related expressions found in text collections.…”
Section: Related Workmentioning
confidence: 99%
“…In the above examples, the patterns that were matched comprise those studied in previous research [3], [5], [6]. These include time-related expressions ("late May," "from December 1," "from March 1, 1996") and future reference expressions ("is expected," "is planned to," "is likely to").…”
Section: Inquiry Into Extracted Future Reference Patternsmentioning
confidence: 87%
“…Alonso et al [4] have indicated that time information included in a document enhances the effectiveness of information retrieval applications. Kanazawa et al [5] focused on extracting unreferenced future time expressions from a large collection of text, and proposed a method for estimating the validity of the prediction by automatically searching for a real-world event corresponding to the predicted one. Jatowt et al [6] studied the relation between future news written in English, Polish, and Japanese using keywords queried on the web.…”
Section: Previous Researchmentioning
confidence: 99%
“…Kanazawa et al [12] estimated that about 30% of predictions in news articles contain future dates based on a small scale investigation. The authors then proposed methods for retrieval and validity analysis of future-related information which is not associated with explicit future dates.…”
Section: Related Workmentioning
confidence: 99%